NILAI TAMBAH PENGOLAHAN DAGING SAPI MENJADI BAKSO PADA USAHA AL-HASANAH DI KELURAHAN RIMBO KEDUI KECAMATAN SELUMA SELATAN - Nasaruddin, Muhammad; Utama, Satria Putra; Andani, Apri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2015)
The aims of this research are to estimate the level of income, and measure the amount of added value obtained from processing beef into meatballs on the business of Al-Hasanah, Rimbo Kedui, South Seluma. Location research and respondents were determined by purposively. The data was collected in the form of primary data, obtained directly from respondents through a questionnaire and interview techniques. The results revealed that during one month processing revenue was Rp. 4.178.194,40 with total receipts amounted Rp.182.700.000,00/month and the total cost reached Rp. 178.521.805,60/month, while the added value obtained for unity input is Rp. 10.052,96/kg with an added value ratio of 8,25% of output produced.